A facile and general approach to enhance the luminescence efficiency and stability of CsPbBr3 perovskite quantum dots. Issue 24 (15th December 2022) - Lu, Yaxian; Guang Jia,; Kong, Hanxiao; Li, Huilin; Zhang, Cuimiao
Abstract: A facile, general, and synthesis method with low-cost has been explored to improve the stability of the CsPbBr3 perovskite quantum dots (PQDs). During the synthesis process, the CsPbBr3 PQDs are encapsulated into the strontium hydroxyapatite (SrHAp) matrix by a direct calcination process under high temperature in the air without any organic solvents, ligands, or polymer additives. The encapsulation strategy not only improves the luminescence efficiency of the PQDs but also greatly enhances their stability for long-term storage. The as-synthesized CsPbBr3 @SrHAp composites possess many advantages including narrow-band emitting, high green color purity, and eminent stability, which may have prospects in the fields of solid-state lighting, optical displays, and optoelectronic devices. Furthermore, this feasible strategy may pave a critical way for improving the stability of all-inorganic CsPbX3 (X = Cl, Br, or I) PQDs.